Psychological gender of sportsmen in team sports - Bojkowski, Łukasz; Kalinowski, Paweł (Akademia Wychowania Fizycznego w Poznaniu)
One of the best-defined concepts of social constructivism is the Gender Schema Theory by Sandra Bem. According to this theory, every person has two dimensions – femininity and masculinity. Basing on their intensity we can distinguish four psychological genders: sex-typed, cross-sex-typed, androgynous and undifferentiated. The aim of this study was to determine the most typical psychological genders characterizing male and female athletes in team sports (football, field hockey, volleyball, basketball, and handball). There were 49 women aged between19 and 32 years old (M = 22.82) and 56 men aged between 18 and 31 years old (M = 21.54) participating in the study. In order to determine psychological genders, we used IPP (Inwentarz do Oceny Płci Psychologicznej) by Kuczyńska. Pearson’s chi2 test showed that in the group of women who play team sports, androgynous psychological gender is the most popular (63.27%). For men who play team sports the most common were: sex-typed (44.64%) and androgynous psychological gender (35.71%)
Keywords: femininity; masculinity; psychological gender; team sports